The Impact of Monetary Policy on Economic Development Goals of Lao PDR - MANIVONG, Soudavong (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The aim of this study is to analyze the impact of monetary policy on the economic development goals of the Lao People's Democratic Republic. The economic development goals used in this study are three: economic growth, inflation, and unemployment. The study uses time series data from 2000-2023 and implies with the SUR model. The economic growth goal was found that only the exchange rate had an impact on economic growth, in the opposite direction and consistent with the hypothesis. Furthermore, the constant coefficient was found to have the largest impact, suggesting that there are other factors besides monetary policy that influence economic growth. For inflation rate goal found that M2 and the exchange rate influence inflation in the same direction and in line with the hypothesis. Interest rates, on the other hand, are not statistically significant. Otherwise, this also indicates that the exchange rate of kip per dollar has a greater influence on inflation than the M2. However, the results of the analysis also show that the fixed coefficient influences inflation in the opposite direction, which means that there are other factors besides monetary policy that lower inflation. Unemployment goal found the M2 also has a negative influence on the unemployment rate, which is consistent with the hypothesis. Meanwhile, the interest rate and the exchange rate have no influence on the unemployment rate.